Neural Basis of Somatosensory Spatial and Temporal Discrimination in Humans: The Role of Sensory Detection. (24th August 2021) - Huang, Cheng-Wei; Lin, Chin-Hsien; Lin, Yi-Hsuan; Tsai, Hsin-Yun; Tseng, Ming-Tsung
Abstract: While detecting somatic stimuli from the external environment, an accurate determination of their spatial and temporal properties is essential for human behavior. Whether and how detection relates to human capacity for somatosensory spatial discrimination (SD) and temporal discrimination (TD) remains unclear. Here, participants underwent functional magnetic resonance imaging scanning when simply detecting vibrotactile stimuli of the leg, judging their location (SD), or deciding their number in time (TD). By conceptualizing tactile discrimination as consisting of detection and determination processes, we found that tactile detection elicited activation specifically involved in SD within the right inferior and superior parietal lobules, 2 regions previously implicated in the control of spatial attention. These 2 regions remained activated in the determination process, during which functional connectivity between these 2 regions predicted individual SD ability. In contrast, tactile detection produced little activation specifically related to TD. Participants' TD ability was implemented in brain regions implicated in coding temporal structures of somatic stimuli (primary somatosensory cortex) and time estimation (anterior cingulate, pre-supplementary motor area, and putamen). Together, our findings indicate a close link between somatosensory detection and SD (but not TD) at the neural level, which aids in explaining why we can promptly respond toward detected somatic stimuli.